Process estimates of recollection and familiarity in working memory and episodic memory - Loaiza-Kois, Vanessa Maria, author; Rhodes, Matthew G., advisor; Cleary, Anne M., committee member; Kraiger, Kurt, committee member; Diehl, Manfred, committee member (Colorado State University. Libraries, 2012)
Working memory is consistently shown to be related to episodic memory, but the underlying processes that contribute to this relationship are poorly understood. The following dissertation outlines a study which investigated the relationship between working memory and episodic memory, with particular regard to the contribution of familiarity and recollection processes to both constructs. Updating measures were also included to examine the potential mediating effects of updating on the relationship between working memory and episodic memory. Measurement models of both task performance and process estimates indicated a three-factor solution, with separate working memory, updating, and episodic memory factors. Such findings suggest that working memory, updating, and episodic memory are related but distinguishable constructs at the latent level of both task and process estimate.
Keywords: structural equation modeling; memory; working memory; episodic memory; factor analysis